2018
DOI: 10.1080/02770903.2018.1493602
|View full text |Cite
|
Sign up to set email alerts
|

The role of asthma in caries occurrence – meta-analysis and meta-regression

Abstract: This study provides reliable and robust evidence that emphasizes the impact of asthma on the occurrence of dental caries in both, primary and permanent, dentitions. The findings provide useful data for recommending that dentists and physicians collaborate to establish the control for both diseases in a multidisciplinary manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
2
17
1
5
Order By: Relevance
“…Other studies have reported similar findings. 19,[21][22][23] Alaki et al, revealed that the lactobacilli and streptococci count increased significantly with the combination of beta 2 agonists and corticosteroids in asthma patients after two years of treatment. This was because the long-term use of corticosteroids caused immunosuppression, resulting in a greater bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported similar findings. 19,[21][22][23] Alaki et al, revealed that the lactobacilli and streptococci count increased significantly with the combination of beta 2 agonists and corticosteroids in asthma patients after two years of treatment. This was because the long-term use of corticosteroids caused immunosuppression, resulting in a greater bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been found in this study. Prolonged use of asthmatic medications can reduce secretion rates of whole and parotid saliva in asthmatics when compared to the nonasthmatic 5,17 …”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis and meta‐regression emphasize and validate the previously stated effect of asthma on the occurrence of caries. It further suggested studies to establish the mechanisms underlying this relation 17 . Hence, this study was conducted with the research hypothesis as “There is an impact of asthma and its medication on salivary characteristics (flow rate, pH, buffer capacity, and Streptococcus mutans and Lactobacillus count) and dental caries in adolescents.”…”
Section: Introductionmentioning
confidence: 99%
“…Por este motivo, es imposible prevenir su contacto con los tejidos dentales duros y la mucosa oral, esto se agrava debido a que en la mayoría de casos los pacientes pediátricos no usan correctamente los inhaladores y la mayor cantidad del medicamento queda disperso en la cavidad oral. (20) Además, el tratamiento inhalatorio con agonistas β2 y corticoesteroides reduce la tasa de secreción salival, disminuye el pH y altera la composición salival. Como lo reportado por Bozejac et al (21) , quienes encontraron que los pacientes con asma moderado persistente y en tratamiento de más de cinco años con diferentes combinaciones de inhaladores como salmeterol + fluticasona, budesonida + formoterol, beclometasona + formoterol y bromuro de ipratopio + fenoterol redujeron significativamente la tasa de secreción salival (0,279 mL/min) en comparación a los pacientes sanos (0,496 mL/min); p=0,001.…”
Section: Discussionunclassified
“…La mejora puede lograrse si los programas de prevención y atención de la salud dental se implementan a mayor escala, dentro de todo el país o región. (20)…”
Section: Discussionunclassified